Lung transplantation after ex vivo lung perfusion in two Scandinavian centres. (29th October 2018) - Nilsson, Tobias; Wallinder, Andreas; Henriksen, Ian; Nilsson, Jens Christian; Ricksten, Sven-Erik; Møller-Sørensen, Hasse; Riise, Gerdt C; Perch, Michael; Dellgren, Göran
Abstract: OBJECTIVES: We reviewed our combined clinical outcome in patients who underwent lung transplantation after ex vivo lung perfusion (EVLP) and compared it to the contemporary control group. METHODS: At 2 Scandinavian centres, lungs from brain-dead donors, not accepted for donation but with potential for improvement, were subjected to EVLP ( n = 61) and were transplanted if predefined criteria were met. Transplantation outcome was compared with that of the contemporary control group consisting of patients ( n = 271) who were transplanted with conventional donor lungs. RESULTS: Fifty-four recipients from the regular waiting list underwent transplantation with lungs subjected to EVLP (1 bilateral lobar, 7 single and 46 double). In the EVLP and control groups, arterial oxygen tension/inspired oxygen fraction ratio at arrival in the intensive care unit (ICU) was 30 ± 14 kPa compared to 36 ± 14 ( P = 0.005); median time to extubation was 18 h (range 2–912) compared to 7 (range 0–2280) ( P = 0.002); median ICU length of stay was 4 days (range 2–65) compared to 3 days (range 1–156) ( P = 0.002); Percentage of expected forced expiratory volume at 1s (FEV1.0 %) at 1 year was 75 ± 29 compared to 81 ± 26 ( P = 0.18); and the 1-year survival rate was 87% [confidence interval (CI) 82–92%] compared to 83% (CI 81–85), respectively. Follow-up to a maximum of 5 years did not show any significant difference in survival between groups (log rank, P = 0.63). CONCLUSIONS: Patients transplanted with lungs after EVLP showed outcomes comparable to patients who received conventional organs at medium-term follow-up. Although early outcome immediately after transplantation showed worse lung function in the EVLP group, no differences were observed at a later stage, and we consider EVLP to be a safe method for increasing the number of transplantable organs.